A Control Approach of the Roof in No-Pillar Roadway Formed by Roof Cutting and Pressure Releasing - Qingnan Lou; Tingchun Li; Qingwen Zhu; Shanyuan Wu; Ming Yun; Renle Zhao (Geofluids)
Roof control is one of the eternal themes of mine pressure theory, and it is also a key step of roadway formed by roof cutting. Based on the analysis of abutment pressure distribution, the viewpoint of controlling roadway roof by roof cutting distance is put forward according to the failure limit of roadway roof, and the calculation method of roof cutting distance is given. Based on the Qiuji coal mine’s background, the numerical and field test study is conducted to verify the theoretical analysis, and the allowable variation range of roof cutting distance is obtained. The research shows that the roof cutting distance, abutment pressure, and roadway deformation are closely related. By controlling the roof cutting distance, the roadway roof can be placed in the low-stress area, the roadway deformation can be reduced, and the support cost can be saved. This study provides a theoretical basis for explaining the roadway’s abnormal mine pressure and controlling the roadway roof by roof cutting.